Efektivitas Penerapan Model Discovery Learning Berbantuan Geogebra - Suradi; Ahmad Zaki; Ghina Farida (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This study aims to determine the effectiveness of the application of the GeoGebra-assisteddiscovery learning model to learning outcomes in mathematics for grade VIII junior high school studentswith indicators of learning effectiveness, namely student learning outcomes, student activities, andstudent responses. This study is a pre-experiment with a quantitative approach to a one group pretest-posttest design using cluster random sampling techniques. The population in this study was students inclass VIII junior high school, and the research sample consisted of one experimental class group of 23students. Pretests and posttests were used to collect data on student learning outcomes; student activityobservation sheets were used to collect data on student activity; and student response questionnaireswere used to collect data on student response. The data were analyzed using descriptive statistics andinferential statistics so that, in general, it can be concluded that the application of the GeoGebra-assisteddiscovery learning model is effectively applied to mathematics learning for grade VIII junior high schoolstudents.